Analysis of the Critical Role Of Organizational Culture in Improving Employee Performance - Wahyudi, Yuli; Pratama, Guruh Dwi; Mulyani, Sri; Seta, Anggada Bayu; Maswatu, Aruji (Universitas Pamulang, 2024)
This research aims to investigate the implementation of the role of organizational culture in strengthening the social responsibility attitudes of the management of the Political Science and Government Study Program Student Association (HIMA PPKn). Higher education has an important role in forming a young generation who has social awareness and responsibility towards society. In this context, student organizations such as HIMA PPKn can be an effective forum for training students in understanding and practicing their social responsibilities. This research uses qualitative methods with data collection techniques through in-depth interviews, observation and document analysis. The main respondents in this research were HIMA PPKn administrators who were active in organizational activities. The research results show that organizational culture plays a significant role in influencing the social responsibility attitudes of HIMA PPKn administrators. A strong organizational culture, which prioritizes values such as participation, cooperation, leadership and openness, encourages HIMA PPKn administrators to care more about social issues and be more actively involved in social activities outside the campus environment. The results of this research provide an important contribution to understanding the importance of organizational culture in the context of student organizations and how organizational culture can influence social responsibility attitudes. These findings can be the basis for developing more effective education and training programs to produce a younger generation who are more socially responsible and care about society. In addition, the results of this research can provide guidance for administrators of other student organizations in optimizing the role of organizational culture in strengthening their social responsibility attitudes.